PENGARUH HUTANG LUAR NEGERI, PENANAMAN MODAL ASING, DAN TABUNGAN DOMESTIK TERHADAP PERTUMBUHAN EKONOMI INDONESIA (1976 - 2000) - Basuki Rahmad; Yuni Prihadi Utomo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2005)
Indonesian economic development along with economic growth needs sustainable development funding sources. This research examines the effect of developmental funding sources such as international debt, foreign investment, and domestic saving toward the development of Indonesian economy.The analysis instrument of the research is double linier regression with ECM model (Error Correction Model). ECM model is an econometric model that can be used to search for regression equations of short term and long-term balance. The data employed are data time series gathered with annual method starting from 1976 to 2000. These data are a secondary data obtained from the financial reports of Indonesian Bank and Statistics Center Agency. Furthermore, to reveal whether the estimation result can be trusted, the researcher performs classical assumption test and statistical test. The analysis result shows that the three factors of funding source for economic development above have significant effect toward the growth of Indonesian economy.